UPAYA PENGHIJAUAN EKOSISTEM MANGROVE DI KAWASAN PESISIR DESA PURWOREJO KECAMATAN PASIR SAKTI KABUPATEN LAMPUNG TIMUR PROVINSI LAMPUNG - Maulid Wahid Yusup; Sri Wahyu Dwi Lestari Ningsih; David Febriansyah; Muhammad Arivin; Galuh Rinjani (Agriculture Faculty, Universitas Lampung, 2026)
Fisheries and Marine Conservation (Fic) is a community service activity in Purworejo Village, Pasir Sakti District, East Lampung Regency, focusing on mangrove planting. A total of 2024 Rhizophora sp. seedlings were planted with the theme “Improving Sustainable Ecosystem Through Mangrove Reforestation”. This activity aims to support ecosystem recovery and provide ecological and social impacts for the surrounding community. The planting location is ±2 km from the land line, has a muddy substrate and is periodically flooded, making it suitable for mangrove growth. The problem of dead vegetation was addressed through land clearing. The direct planting method was used, with the planting direction parallel to the shoreline. The planting pattern refers to a scientific approach with a high survival rate. Eight plots were prepared, each containing 253 seedlings. A follow-up phase of monitoring and evaluation was conducted to measure success and develop improvements and innovations in mangrove conservation in the future.